F-18 FDG PET-CT Influences Target Delineation When Combined With Standard CT-Based Radiotherapy Planning in the Palliative Setting in Malignant Pleural Mesothelioma; an Exploratory Study - Mac Leod, Nicholas; Stobo, Jon; O’Rourke, Noelle; Hicks, Jonathan; Moore, Karen; Sankaralingam, Marimuthu; Oommen, Kurian; Kelly, Caroline; McMahon, Lynn; Wi Poon, Fat; et al. (Reports of Radiotherapy and Oncology, 2015)
Background: Positron emission tomography computerized tomography (PET-CT) is useful in radiotherapy planning for lung cancer. However, its role in malignant pleural mesothelioma (MPM) is unknown. Objectives: This exploratory study investigated the possible role for PET-CT in radiotherapy planning for MPM. Patients and Methods: Patients receiving radiotherapy for the treatment of pain in MPM, had fluorodeoxyglucose (FDG) PET-CT scanning in addition to their standard CT scan. PET-CT images were then fused with CT planning images, termed Planning-PET-CT. Target volume delineation was undertaken first using CT and subsequently incorporated Planning-PET-CT. Planning treatment volume (PTV), conformity index (CI), mean distance to conformity (MDC), center of gravity distance (CGD) and standard uptake values (SUV) were examined. Results: Sixteen patients were recruited into the study. PET-CT upstaged nine patients. No association between SUV max and either survival or pain response was seen. Volumes contoured using Planning-PET-CT differed markedly from those outlined using CT alone as shown by the following parameters: CI = 0.3 (0.24 - 0.38). MDC = 21.47 (16.73 - 33.70) and CGD = 16.40 (11.80 - 33.87). The median percentage of over contouring was 44.00% (34.33 - 72.50) with 46.67% under contoured (34.00 - 55.00). Conclusions: PET-CT alters the position of the PTV in MPM and upstaged a proportion of patients. Further work to elucidate the role of Planning-PET-CT in target volume definition is justified.